Dancing wisdom: embodied knowledge in Haitian vodou, Cuban yoruba, and Bahian candomblé - Daniel, Yvonne (University of Illinois Press, 2005)
Deciphering diaspora dances: their origin nations and belief systems -- Body knowledge at the crossroads -- Days of remembrance -- Dances of memory -- Praise dance and liturgical orders -- Informal learning with Haitian lwas -- Informal learning with Bahian orixás -- Formal learning with Cuban orichas -- The dancing body and embodied wisdom